Genres of Secular Instruction: A Linguistic History of Useful Entertainment - Irma Taavitsainen (Miscelánea: A Journal of English and American Studies, 2004)
The aim of this paper is to outline a history of useful entertainment through genres of secular instruction. My focus is on Late Medieval and Early Modern texts, but I shall touch upon a longer diachrony as well. I shall first go through the title word by word, to explain my method of analysis and approach, and show how useful entertainment and instruction are linked in the history of English. In the empirical part of my paper I shall focus first on discourse forms and then on the linguistic features of some typical texts.
Keywords: entertainment; genre; secular instruction; Late Medieval/Early Modern texts